Moisture content of kenaf (hibiscus cannabinus l.) stem based on microwave dielectric properties - Radzuan, Mohd Nazren (2013)
This research investigated the relationship between microwave the dielectric properties of kenaf plant and it‘s MC for purpose of developing an in-situ sensor for the measurement of kenaf stem fibre MC. The rectangular waveguide resonator method was used to determine the dielectric properties of kenaf stems and the results were compared with those of the oven dried method of various drying times. The relationship between the dielectric properties and MC and frequency were investigated. The dielectric constant, ε‘ and loss facor, ε‖ in the kenaf stem, core and bast at frequencies 8.7875 GHz and 10.1882 GHz showed cubic relationship with MC. The equation for in-situ MC determination in kenaf stem was established and compared with those of the conventional drying method to evaluate the accuracy of the new equation established. The R2 value for kenaf stem samples at B, M and T portion at frequency show strong relationship that is above 0.9 compared with kenaf core and bast samples. In bast, the correlation between dielectric properties with MC was not good thus the MC determination equation cannot be established. The ability of this technique to determine the kenaf stem MC accurately and rapidly will not only help in improving the efficiency of decorticator machine in kenaf processing,but also in improving fibre quality and market price of kenaf fibre.